Niche vs Mass marketing : A profit and entrepreneurial analysis in the music industry - Bansal, Shashwat; Ryška, Tomáš, 1976-; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The main objective of this thesis is to assess why specific musicians are famous in the masses and why certain musicians are not. It also attempts to assess why some musicians are only successful in the niche part of the music industry and their incentives or what forces them to stay there. I restrict the research to music category - electronic music, and musicians – Disk Jockeys (DJs). The structure of the thesis is such that it tries to explain the entire scenario of the music business and the various paradigms on which the industry operates. It takes on an economic, cultural, psychological, and ethnographic perspective of the demand and supply of music as a commodity and/or service. I also try to do an analysis of the complimentary services attached with it. Finally, the research gives some innovative recommendations which budding and existing musicians can use to gain a competitive advantage.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses